Terapi Senam untuk Mengurangi Keluhan Selama Masa Nifas - nadhiroh, aim matun (Universitas Muhammadiyah Surabaya, 2022)
Objective: Most postpartum mothers experience a decrease in their physical, psychological and social conditions while carrying out their new role as mothers. This will affect their psychological condition. Yoga is an alternative to complementary therapy to improve and stabilize the mother's psychological condition. The purpose of this study was to determine the effect of yoga on postpartum mothers on the psychological condition of postpartum mothers. Methods: The research method used is a quasi-experiment with pre-test and post-test of 22 postpartum mothers. The sampling technique is random sampling. This research was conducted from Juli 2019 – December 2019. The research instrument used to measure postpartum maternal anxiety was the Edinburgh Postnatal Depression Scale (EPDS) questionnaire. Data analysis used paired sample t-test and univariate and bivariate data presentation. Results: There is an effect of postnatal yoga on the psychological condition of the mother before and after doing postpartum yoga P value (0.000) < (0.05).Conclusion: There is an effect of postpartum Yoga on postpartum psychological conditions.